Adapting cognitive behavioural therapy for adolescents with psychosis: insights from the Managing Adolescent first episode in psychosis study (MAPS). Issue 1 (2nd January 2023) - Langman-Levy, Amy; Johns, Louise; Palmier-Claus, Jasper; Sacadura, Catarina; Steele, Ann; Larkin, Amanda; Murphy, Elizabeth; Bowe, Samantha; Morrison, Anthony
ABSTRACT: Background: Onset of psychosis commonly occurs in adolescence, and long-term prognosis can be poor. There is growing evidence, largely from adult cohorts, that Cognitive Behavioural Therapy for Psychosis (CBTp) and Family Interventions (FI) can play a role in managing symptoms and difficulties associated with psychosis. However, adolescents have distinct developmental needs that likely impact their engagement and response to talking therapy. There is limited guidance on adapting CBTp to meet the clinical needs of under-eighteens experiencing psychosis. Method: This educational clinical practice article details learnings from therapists and supervisors working with young people (aged 14–18 years) with psychosis during the Managing Adolescent first-episode Psychosis: a feasibility Study (MAPS) randomised clinical treatment trial, supplemented by findings from nested qualitative interviews with young people receiving CBTp. Results: Suggested are given for tailoring CBTp assessment, formulation and interventions to meet the developmental and clinical needs of adolescents with psychosis. Developmentally appropriate techniques and resources described. Conclusions: Early indications from MAPS study indicate this developmentally tailored approach is an acceptable, safe and helpful treatment for young people with psychosis. Further research is needed to develop empirically grounded and evaluated CBTp for adolescents.